#315 : Determination of Clinical Pregnancy and Live Birth Rates in Autologous Cycles for Women Between 40 and 46 Years Old - Lucy Owens; Tegan Ekanayake; Mark Green; Deirdre Zander-Fox; Beverley Vollenhoven (Fertility & Reproduction, 2023)
Background and Aims: It is well-documented that fertility rates decline with maternal age, however there is limited information on the success rates for women between 40 to 50 years old using their own eggs. Many ART providers set differing maternal age limits for accessing treatment, with minimal clinical evidence to support these limits being set. The aim of this study was to identify clinical and live birth rates for women aged 40 to 46 at egg pick-up (EPU), who used autologous oocytes and ET (with or without pre-implantation genetic testing (PGT)). Method: A retrospective cohort study was performed on 7,521 autologous EPU cycles undertaken between 2015 and 2020 for women between 40 and 46 years old at clinics in Victoria, Australia. Maternal age was determined by age at the time of EPU. Clinical pregnancy rate (CPR) and live birth rate (LBR) outcomes were calculated following the transfer of a single fresh or frozen blastocyst stage embryo. Outcomes were also determined for PGT-tested compared with non-PGT-tested frozen embryo transfer (FET) cycles based on maternal age at time of embryo creation and analysed at each age by Fisher’s exact test. Results: CPR and LBR declined with increasing maternal age for both fresh and frozen single blastocyst ETs (Tables 1 and 2), with no live births for women who had eggs collected at 46 years old. Equally, outcomes were lower for fresh compared with frozen ET cycles (P<0.0001). In FET cycles, while LBR declined with age for non-PGT cycles, LBR remained steady and was higher between age 40 and 45 years than when a PGT-tested embryo was transferred (P<0.02). Conclusion: Increasing maternal age at EPU was negatively associated with clinical outcomes, especially after the age of 43 years. Transfer of a PGT-tested embryo did however maintain a high LBR irrespective of maternal age.